Exploring the effects of relational resources and digital capability on entrepreneurial performance based on the mediating role of value creation innovation: A conceptual study - Li Haibo; Noor Fzlinda Fabeil; Salmah Topimin; Ang Hong Loong (Human Resource Management Academic Research Society (HRMARS), 2024)
The aim of this study is to investigate how Chinese small and medium-sized enterprises can enhance their entrepreneurial performance by improving their relational resources and digital capability. While previous research indicates that relational resources and digital capability may not always have a direct impact on entrepreneurial performance, this study proposes a new research framework based on the value creation theory. This framework treats relational resources and digital capability as independent variables, with entrepreneurial performance as the dependent variable. Value creation innovation is introduced as a mediating variable to examine its role in mediating the relationships between relational resources, digital capability, and entrepreneurial performance. The measurement tools were constructed using mature measurement scales to ensure the reliability of research findings. The study's findings contribute to theoretical research on entrepreneurial performance in Chinese small and medium-sized enterprises, providing a solid foundation for future empirical studies.